2005
DOI: 10.1111/j.1525-1438.2005.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma with laparotomy wound recurrence: complete remission following surgery and chemotherapy consisting of paclitaxel and carboplatin

Abstract: We present a patient with surgical stage I endometrial cancer who experienced laparotomy wound recurrence 4 years after primary treatment. She was treated successfully by complete surgical resection of recurrent tumors and chemotherapy. A 62-year-old white female with laparotomy wound recurrence of endometrial carcinoma with small-bowel involvement and concomitant subcutaneous metastasis in the abdominal wall underwent complete surgical resection of metastatic tumors followed by six cycles of chemotherapy cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There is little evidence to support any practice to reduce PSM risk ( Curet, 2004 ). The LAP2 trial reported a low PSM incidence of 0.24%, which is acceptable compared to laparotomy ( Walker et al, 2012 , Gücer et al, 2005 ). Furthermore, the LAP2 trial concluded that the use of MIS was safe regardless of pathological subtype ( Walker et al, 2012 ).…”
Section: Discussionmentioning
confidence: 96%
“…There is little evidence to support any practice to reduce PSM risk ( Curet, 2004 ). The LAP2 trial reported a low PSM incidence of 0.24%, which is acceptable compared to laparotomy ( Walker et al, 2012 , Gücer et al, 2005 ). Furthermore, the LAP2 trial concluded that the use of MIS was safe regardless of pathological subtype ( Walker et al, 2012 ).…”
Section: Discussionmentioning
confidence: 96%
“…[13] We do not use a bag in our routine also because there are not strong evidence to recommend it. EC recurrences may also occur on incisional abdominal wounds/scars of laparotomic or mini invasive primary surgery, usually due to microscopic tumor seeding [26][27][28] : EC seeding on Bartholin's gland incision during preoperative hysteroscopy can also justify VMs. [9] Limited and conflicting data suggested that pneumoperitoneum may alter the peritoneal surfaces, favoring cancer cell adherence.…”
Section: Discussionmentioning
confidence: 99%
“…VMs may be due to direct tumor spread through vagina [10,14], which also represents the most frequently preoperatively-contaminated site because of tumor bleeding [24]. Moreover, EC-recurrences may occur on incisional abdominal wounds/scars of either laparotomy or mini-invasive surgery [21][22][23], usually due to microscopic tumor seeding during primary surgery [9]. EC-seeding on Bartholin's gland incision during preoperative hysteroscopy can also justify VMs [9].…”
Section: Discussionmentioning
confidence: 99%